The Pygmalion Effect to Piano Teaching From the Perspective of Educational Psychology - Qi, Wen; Dong, Xingru; Xue, Xiaoran (Frontiers in Psychology, 2021)
Aiming at the problem of low student enthusiasm in piano teaching, this work tried to apply “Pygmalion effect” to piano teaching from the perspective of educational psychology. Forty-five students were chosen from nine classes in grades 2, 4, and 6 of a central elementary school in Beijing City using experimental research, and the experimental group and the control group were set up. A questionnaire was adopted to conduct the pre-test and post-test of the experiment, which were done to analyze the factors that affect the attitude of students toward music learning and the effect of piano teaching. The results show that the encouragement level of the piano teacher and the enthusiasm of the students in the piano course were significantly correlated at the 0.01 level. There was also a significant correlation between self-efficacy and student piano learning enthusiasm at the 0.01 level. Furthermore, the pre-test and post-test results showed that the students in the experimental group of each grade generally performed much better in piano learning than the students in the control group, which proves that the “Pygmalion effect” can play an excellent interventional role in piano teaching. In this research, the value of “Pygmalion effect” in the educational psychology of piano music education in primary schools was deeply studied to explore the possibility of a novel piano teaching model. The research results show that teacher encouragement can stimulate the subjective initiative of students and make them perform better in piano learning. This research provides reference and ideas for the combination of education- and psychology-related research in the music classroom.